2022
DOI: 10.3389/fcimb.2022.901324
|View full text |Cite
|
Sign up to set email alerts
|

Infection With Escherichia Coli Pathotypes Is Associated With Biomarkers of Gut Enteropathy and Nutritional Status Among Malnourished Children in Bangladesh

Abstract: Escherichia coli (E. coli) pathotypes are the most common cause of diarrhea, especially in developing countries. Environmental Enteric Dysfunction (EED) is presumed to be the result of infection with one or more pathotypes and can affect intestinal health and childhood growth. We sought to investigate the association of E. coli pathotypes infection with biomarkers of EED and nutritional status among slum-dwelling malnourished children in Bangladesh. This study comprised a total of 1050 stunted and at risk of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A similar increase has been previously reported in individuals infected with Shigella [ 47 ], an invasive pathogen that normally causes more severe infections than ETEC. In contrast, previous studies found lower fecal neopterin levels in infants positive for ETEC and other gut pathogens in infants in LMIC [ 8 , 48 ]. This discrepancy can be explained by neopterin functioning as an immunoattractant in circulation rather than secretion into the gastrointestinal tract or biological differences in infants in LMIC.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…A similar increase has been previously reported in individuals infected with Shigella [ 47 ], an invasive pathogen that normally causes more severe infections than ETEC. In contrast, previous studies found lower fecal neopterin levels in infants positive for ETEC and other gut pathogens in infants in LMIC [ 8 , 48 ]. This discrepancy can be explained by neopterin functioning as an immunoattractant in circulation rather than secretion into the gastrointestinal tract or biological differences in infants in LMIC.…”
Section: Discussionmentioning
confidence: 63%
“…S100A9 itself is also known to enhance phagocytosis by neutrophil granulocytes, as reported for E. coli in vivo [ 50 ]. In Bangladesh, higher fecal calprotectin levels have been observed in ETEC-positive infants [ 8 ]. In patients with inflammatory bowel diseases (IBD) with high fecal calprotectin, fecal and plasma calprotectin usually showed positive associations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, having access to a clean latrine has been identified as an important determinant of child malnutrition ( 67 , 68 ). Repeated exposure to fecal matter in an unclean school latrine may result in undernutrition through enteric dysfunction, as pathogenic bacteria present in the feces, such as E. Coli , may damage the intestinal mucosa and prevent nutrient absorption ( 69 , 70 ). Additionally, parasites such as Ascaris lumbricoides shed eggs in feces.…”
Section: Discussionmentioning
confidence: 99%